Development of a Ton Blockchain-Based Online Donation System for Enhanced Transparency - Zaenal Alamsyah; Somantri Somantri; Yoviar Pauzi (bit-Tech, 2025)
Online donation platforms in Indonesia despite the nation’s leading position in the 2024 World Giving Index continue to suffer from low public trust due to insufficient transparency in fund management. This lack of verifiability creates opportunities for fraud and misuse, ultimately deterring donor participation. Addressing this challenge, the present study proposes a novel blockchain-based donation system built on The Open Network (TON), specifically designed to embed transparency, accountability, and trust directly into the donation process through decentralized mechanisms. Unlike previous platforms that rely on centralized fund tracking, this system integrates smart contracts programmed in the Tact language to automate and enforce donation logic without human intervention. Core functionalities include campaign creation, donation receipt, fund withdrawal, and balance transfers all of which are transparently recorded and publicly accessible on the blockchain. The system achieved 100% functional suitability and a 94% usability score, based on evaluations involving 36 participants, while all 14 smart contract unit test scenarios returned successful outcomes. These results highlight the platform’s robustness and user acceptance. By enabling tamper-proof transaction records and public verifiability through the TON Explorer, the proposed platform demonstrates strong potential for restoring donor trust and setting new standards for transparency in digital philanthropy. The study contributes both a practical system prototype and theoretical insights into blockchain’s role in reengineering trust within charitable ecosystems, offering a replicable model for future philanthropic technologies in Indonesia and beyond.